INVESTMENT DECISIONS OF YOUNG INDONESIAN INVESTORS: THE INFLUENCE OF FINANCIAL LITERACY, OVERCONFIDENCE, AND RISK TOLERANCE - Erna Garnia; Ajeng Aprilia; Siti Riyyan Lisaumi (Multifinance, 2025)
Economic growth in a country can originate from investment activities. Every year, the number of investors in the capital market continues to increase, and these investors are predominantly young investors. Investment activities are inseparable from the investment decision-making process itself. However, in determining investment decisions, investors are influenced by both rational and irrational factors. This study aims to analyze and describe the influence of financial literacy, overconfidence, and risk tolerance on investment decisions among young investors in investment galleries throughout the Greater Bandung area. This research employs descriptive and verificative approaches using primary data and a quantitative methodology. The sampling method utilized is purposive sampling. Data testing and analysis include validity tests, reliability tests, classical assumption tests, multiple linear regression analysis, correlation coefficient analysis, coefficient of determination analysis, and hypothesis testing. The research findings demonstrate that financial literacy, overconfidence, and risk tolerance have a significant positive influence both simultaneously and partially on investment decisions among young investors in investment galleries throughout Greater Bandung. These results indicate that enhancing financial literacy, managing overconfidence behavior, and understanding individual risk tolerance profiles are crucial factors in improving the quality of investment decision-making among young investors in Indonesia's emerging capital market.